2020
DOI: 10.3390/ijms21124240
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Autophagy Causes Superoxide Formation and Caspase Activation in 661 W Cells, a Cell Line for Cone Photoreceptors, under Hyperglycemic Conditions

Abstract: Microvascular changes are the earliest adverse events in diabetic retinopathy, but recent studies have shown that oxidative stress induced by photoreceptors is associated with the development of the retinopathy. The purpose of this study was to determine the roles played by superoxides formed by photoreceptors under hyperglycemic conditions on autophagy. To accomplish this, we cultured 661 W cells, a transformed murine cone cell line, with 5.5 or 25 mM glucose in the presence or absence of 3 methyl adenine (3M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In a recent study, Taki and co-workers (2020), using 661W cells, a transformed murine cone cell line, observed that HG treatment (25 mM, 48 h) induced changes in mitophagy and autophagy with mitochondria accumulation and upregulation of p62. Treatment with 3-MA caused a greater increase of p62, superoxides and caspase 3/7 activation suggesting that impairment of the autophagy pathway correlates with superoxide formation and induction of apoptosis (Taki et al, 2020).…”
Section: Mitophagy and Diabetic Retinopathymentioning
confidence: 93%
“…In a recent study, Taki and co-workers (2020), using 661W cells, a transformed murine cone cell line, observed that HG treatment (25 mM, 48 h) induced changes in mitophagy and autophagy with mitochondria accumulation and upregulation of p62. Treatment with 3-MA caused a greater increase of p62, superoxides and caspase 3/7 activation suggesting that impairment of the autophagy pathway correlates with superoxide formation and induction of apoptosis (Taki et al, 2020).…”
Section: Mitophagy and Diabetic Retinopathymentioning
confidence: 93%
“…Although the mechanism by which autophagy protects photoreceptors and the relationship between DR and autophagy are ambiguous, more recent studies have corroborated the importance of autophagic flux. For example, impairment of autophagy increases superoxide formation and apoptosis in 661 W cells (a cone cell line) under hyperglycemic conditions ( Taki et al, 2020 ).…”
Section: Involved Cellsmentioning
confidence: 99%
“…Abbreviations: AMD, age-related macular degeneration; CNV, choroidal neovascularization; EGCG, epigallocatechin gallate; HG, high glucose; GA, geographic atrophy; MMXM, Mingmu Xiaomeng; OCT, octreotide; OPTN, optineurin; RGC, retinal ganglion cell; rMCs, retinal Müller cells. References in the figure: 1992 [ 55 ], 1990 [ 60 ], 1991 [ 1 ], 1997 [ 63 ], 2002 [ 61 ], 2009 [ 159 ], 2010 * [ 162 ], 2010 ** [ 161 ], 2013 * [ 160 ], 2013 ** [ 123 ], 2014 * [ 146 ], 2014 ** [ 16 ], 2015 * [ 44 ], 2015 ** [ 94 ], 2016 * [ 120 ], 2016 ** [ 83 ], 2018 [ 89 ], 2019 * [ 19 ], 2019 ** [ 136 ], 2021 * [ 153 ], 2021 ** [ 28 ], 2021 *** [ 91 ].…”
Section: Figurementioning
confidence: 99%